Effect of Different Customized Abutment Types on Stress Distribution in Implant‐Supported Single Crown: A 3D Finite Element Analysis. Issue 5 (16th May 2022) - Pumnil, Suphakrit; Rungsiyakull, Pimduen; Rungsiyakull, Chaiy; Elsaka, Shaymaa
Abstract: Purpose: The purpose was to investigate stress distribution among 4 different customized abutment types: titanium abutment (Ti), titanium hybrid‐abutment‐crown (Ti‐Hybrid), zirconia abutment with titanium base (Zir‐TiBase), and zirconia hybrid‐abutment‐crown with titanium base (Zir‐Hybrid‐TiBase). Materials and methods: To achieve this purpose, 4 types of abutment configurations were simulated. A static load of 200 N (vertical) and 100 N (oblique) were applied to the models. The volume average, maximum, and stress distribution of von Mises stress, including percentage difference, were analyzed with 3D finite element analysis. Results: According to the volume average von Mises stress, the Ti and Zir‐TiBase comparison group showed that the Zir‐TiBase group dominantly generated the higher value at Ti‐base (22.57 MPa) and screw (17.68 MPa). To evaluate the effect of the hybrid‐abutment‐crown on volume average von Mises stress by comparing the Ti‐Hybrid and Zir‐Hybrid‐TiBase groups, it was revealed that the combination of abutment and crown in the Ti‐Hybrid group generated the worst stress concentration at the screw (12.42 MPa), while in the Zir‐Hybrid‐TiBase group presented stress concentration at the implant (8.90 MPa). Conclusions: A titanium base improved stress distribution at implant in zirconia abutment with titanium base by absorbing stress itself. Customized titanium hybrid‐abutment‐crown and zirconia hybrid‐abutment‐crown with titanium base created concentrated stress at screw and implant; respectively. Both abutment types should be cautiously used and maintenanced regularly.